Ação de classe em matéria tributária como instrumento de acesso à justiça - Ferreira Filho, Roberval Rocha (2009)
With the advent of mass society, marked by high litigiosity and complexity of the social relations, the traditional techniques of conflict’s resolutions have revealed insufficient to protect the social peace. As a result of this, the common law old procedural institute of class actions resurged with force. In the last decades, the class action institute has been spread in all world as an effective technique to combat the litigiosity and to improve the access of justice. Absorbed by almost all the legal systems, the class actions had operated significant changes in the protection of the metaindividual rights. However, in the Brazilian legal system, although the recent legislative advances, the use of class actions has not achieved all the legal subsystems, as the tax law system, where the phenomenon of the litigiosity, of the legal relationships complexity, and the mass actions are rule. The analysis of this situation, including the necessity of the use of this type of legal action to strengthen citizenship and to mitigate the litigiosity in the relations Statetaxpayer, is the target of the present work.